Analisis Dampak Akreditasi dalam Peningkatan Mutu Pendidikan di Paud X Kota Pangkalpinang - Jurdis Rizky Kumala; Arif Hakim (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. This thesis research wants to describe and examine the impact of accreditation in improving the quality of education at the Tamasha Valaq PAUD institution, Pangkalpinang city. This thesis uses qualitative research with case study research methods. Data were collected in three ways, namely (1) Interview, (2) Documentation, (3) Observation. Furthermore, the data that has been collected is analyzed with the flow of (1) data reduction, (2) data display, (3) conclusion. The results of the research found are as follows (1) seen from the eight national quality standards of early childhood education, 90% have met the existing standards. This is reflected in every implementation of the eight educational qualities. Although there is one standard that is not in accordance with the existing educational quality standards, the institution continues to strive to improve educational services so that the quality of education at the institution can still be achieved. (2) accreditation has a positive impact on the institution. This can be seen from the physical evidence displayed by the institution, starting from adequate and complete facilities and infrastructure, improving teacher performance, and increasing trust from the community and government. The institution continues to strive to increase the productivity of its institution in order to achieve the expected quality of education. The institution involves all elements of the school to continue to maintain and improve the quality of education so that the next accreditation will remain in a proper condition from all aspects of the quality of education. Abstrak. Penelitian skripsi ini ingin mendeskripsikan dan mengkaji dampak dari akreditasi dalam peningkatan mutu pendidikan di lembaga PAUD X kota Pangkalpinang. Skripsi ini menggunakan penelitian kualitatif dengan metode penelitian studi kasus. Data dikumpulkan melalui tiga cara yaitu (1) Wawancara, (2) Dokumentasi, (3) Observasi. Selanjutnya data yang telah terkumpul dianalisis dengan alur (1) Reduksi data, (2) Display data, (3) Kesimpulan. Hasil penelitian yang ditemukan adalah sebagai berikut (1) dilihat dari delapan standar nasional mutu pendidikan anak usia dini 90% telah memenuhi standar yang ada. Hal ini tergambar didalam setiap pelaksanan delapan mutu pendidikan tersebut. Walaupun terdapat satu standar yang kurang sesuai dengan standar mutu pendidikan yang ada, namun lembaga terus berupaya untuk meningkatkan pelayanan pendidikan agar tetap tercapainya mutu pendidikan di lembaga tersebut.(2) akreditasi memberikan dampak yang positif bagi lembaga. Hal ini dilihat secara bukti fisik yang ditampilkan oleh lembaga mulai dari sarana dan prasarana yang memadai dan lengkap, peningkatan kinerja guru, dan kepercayaan dari masyarakat dan pemerintah yang semakin tinggi. Lembaga terus berupaya untuk meningkatkan produktivitas lembaganya agar tercapai mutu pendidikan yang diharapkan. Lembaga melibatkan seluruh unsur sekolah untuk terus mempertahankan dan meningkatkan mutu pendidikan agar pada akreditasi berikutnya tetap dalam keadaan layak dari segala segi mutu pendidikan.